SONLU BİR ARALIKTA SÜREKSİZLİĞE SAHİP DİFERENSİYEL DENKLEM İÇİN TERS PROBLEM - KULA, ENDER (Fırat Üniveristesi, 2023)
Bu çalışmada, sonlu bir aralığın orta noktasında süreksizlik sınır şartına sahip bir Sturm-Liouville problemi için ters nodal problemin çözümü verilmiştir. Bunun için Prüfer dönüşümü kullanılmıştır. Öncelikle bu dönüşüm yardımıyla özdeğerler, özfonksiyonların sıfırları (nodal noktalar) ve nodal uzunluklar için asimptotik formlar bulunmuştur. Sonraki aşamada: Nodal parametreler yardımıyla potansiyel fonksiyon için bir formül verilmiştir.

In this study, the solution of the inverse nodal problem is given for a Sturm-Liouville problem with a discontinuity boundary condition at the midpoint of a finite interval. For this, Prüfer transform is used. First of all, with the help of this transformation, asymptotic forms for eigenvalues, zeros of eigenfunctions (nodal points) and nodal lengths are found. In the next step: a formula for potential function is given with the help of nodal parameters.
Inverse problem for a differential equation with discontinuity in a finite range
Keywords: Matematik